Comparative effect of seven prophylactic locks to prevent biofilm biomass and viability in intravenous catheters. (20th June 2022) - Austin, Peter David; Stapleton, Paul; Elia, Marinos
Abstract: Background: Patients requiring long-term intravenous access are at risk of intraluminal catheter bloodstream infection. 'Prophylactic' locks aim to limit this risk but there is uncertainty regarding the most effective lock. Objectives: To develop a novel technique intended to replicate clinical procedures to compare the effectiveness of various 'prophylactic' locks against biofilm biomass ('biomass') formation and biofilm viability ('viability') of Escherichia coli and Staphylococcus epidermidis in intravenous catheters. Methods: For 10 consecutive days 10 6  cfu/mL E. coli NCTC 10418 and S. epidermidis ATCC 12228 were separately cultured in single lumen 9.6 French silicone tunnelled and cuffed catheters. These were flushed with 0.9% w/v sodium chloride using a push–pause technique before and after instillation of seven 'prophylactic' locks (water, ethanol, sodium chloride, heparinized sodium chloride, citrate, taurolidine plus citrate, and taurolidine; each in triplicate) for 6 h daily. Intraluminal 'biomass' and 'viability' were quantified using crystal violet staining and flush culture, respectively. Results: The reduction of 'biomass' and 'viability' depended on both agent and species. Citrate was least effective against E. coli 'viability' and 'biomass' but most effective against S. epidermidis 'viability', and taurolidine was most effective against E. coli 'biomass' and 'viability' but least effective against S. epidermidis 'viability'. 'Biomass' and 'viability' were significantly correlated in E. coli between ( r  = 0.997, P  < 0.001) and within ( r  = 0.754, P  = 0.001) interventions, but not in S. epidermidis . Conclusions: A novel technique found the effect of 'prophylactic' agents in reducing 'biomass' and 'viability' varied by species. The choice of agent depends on the most likely infecting organism.